Answer:
![x_1=-6.9\\x_2=0.9](https://img.qammunity.org/2020/formulas/mathematics/middle-school/29jccv34usv5bscbok38u1z95rmc5eevj2.png)
Explanation:
The first step is to move all the terms from the right side to the left side of the equation and then add the like terms:
![2x^2+12x-16=-3\\\\2x^2+12x-16+3=0\\\\2x^2+12x-13=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4mrx8xooc1330qi0xw6iazky3swcvjalw7.png)
Now we can apply the Quadratic formula. This is:
![x=(-b\±√(b^2-4ac))/(2a)](https://img.qammunity.org/2020/formulas/mathematics/college/nzmxzqefv733aqje6pzhmymg6dznp7bpm5.png)
In this case we can identify that:
![a=2\\b=12\\c=-13](https://img.qammunity.org/2020/formulas/mathematics/middle-school/psv6st7eirhp9jq1rq0nz9aczdg9zlt9a0.png)
Finally, we must substitute these values into the Quadratic formula. Then we get:
![x=(-12\±√(((12)^2-4(2)(-13)))/(2(2))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/tqgabi44e95ww9cpltvmdabtc16lb5rq6j.png)
![x_1=-6.9\\x_2=0.9](https://img.qammunity.org/2020/formulas/mathematics/middle-school/29jccv34usv5bscbok38u1z95rmc5eevj2.png)